Effect of hip joint mobilizations and strength training on pain, physical function and dynamic balance in patients with Knee Osteoarthritis: a randomized controlled trial - Mehwish, Bushra; Ali, Syed Shahzad; Ahmed Mirza Baig, Aftab (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the effects of hip joint mobilisations and strengthening exercises on pain, physical function and dynamic balance in patients with knee osteoarthritis. Method: The single-blind three-arm parallel randomised controlled trial was conducted at Sindh Institute of Physical Medicine and Rehabilitation, the outpatient department of Dow University of Health Sciences’ Ojha Campus, Rabia Moon Memorial Welfare Trust and the Civil Hospital, Karachi, from January to July 2021. The sample comprised patients aged at least 50 years having knee osteoarthritis grade 1-3. The patients were randomised into 3 equal groups, with group A receiving hip mobilisations along with strengthening exercises of hip and conventional knee exercises, group B receiving strengthening exercises of hip along with conventional knee interventional exercises, and group C receiving conventional knee exercises only. Pain, physical function and dynamic balance were assessed using visual analogue scale, knee injury osteoarthritis outcome score and four-step square test, respectively, at baseline and after 18th session. Data was analysed using SPSS 21. Results: Of the 74 subjects assessed, 66(89.2%) were included; 22(33.3%) in each of the three groups. The sample had 19(28.8%) male subjects and 47(71.2%) female. The mean age in groups A, B and C were 55.64±3.56 years, 53.64±4.65 years and 54.91±4.30 years, respectively. There was significant difference among groups post-treatment (p<0.001). Significant improvement was also found in inter-group analyses of all outcomes (p<0.001). Conclusion: Addition of hip joint mobilisations provided better results compared to the other two groups. Clinical Trial Number: https://clinicaltrials.gov/ct2/show/NCT04769531. Key Words: Clinical trial Manual therapy, Knee osteoarthritis, Lower extremity manual therapy, Musculoskeletal, Posture, Resistance training.